Ipsilateral femoral shaft and medial Hoffa fracture in a 13-year-old male following road traffic accident - Kumar, Pankaj; Kumar, Nitish (International Journal of Research in Orthopaedics, 2025)
Hoffa fractures, particularly of the medial femoral condyle, are rare in pediatric populations. Their association with ipsilateral femoral shaft fractures is exceedingly uncommon. We present a case of a 13-year-old boy who sustained an ipsilateral femoral shaft fracture and medial Hoffa fracture following a high-energy road traffic accident (RTA). The shaft fracture was managed with closed reduction and titanium elastic nailing (TENs), and the medial Hoffa fracture was treated via open reduction and internal fixation with cannulated Herbert screws using a medial parapatellar approach. This report highlights the importance of high clinical suspicion and appropriate imaging to diagnose these rare injury patterns.